(untitled) (Editora Impacto Científico, 2025)
Among the various conceptions regarding the human person, it is believed that Boethius’s definition was the one that received the greatest emphasis, at least in the Christian West, precisely because it affirms that the human being is an individual substance of a rational nature. However, this thought was the target of numerous criticisms, which only Saint Thomas Aquinas was able to fully address by affirming, above all, that the human person is the most perfect being in all of nature, namely, that which subsists individually in a rational nature. In the present chapter, carried out through a literature review, the objective was to understand and explain what the medieval philosopher Saint Thomas Aquinas thought regarding the human person. His first steps in his studies were decisively influenced by Aristotle. His main philosophical works identify him as someone who contributed mainly from an ontological-metaphysical perspective to address this important problem of the conception of the person. Nevertheless, it continued to be a very difficult and much-discussed issue. Focusing more on the person from the Thomistic anthropological perspective, without forgetting that the chosen theme is eminently philosophical, when conceptualizing the “human person,” Saint Thomas took such a definition from God as the perfect Being. It is precisely because man is a “person” that he stands at the apex of beings in the universe, as he is considered to be in the image and likeness of God. This leads to the reflection that the personality of the human being is found primarily in God. However, the condition of being a person in God can only be attained through reason, since it is reason that distinguishes us from other beings and renders each one worthy, despite imperfections. DOI: https://doi.org/10.56238/edimpacto2025.090-004